THE IMPACT OF WORK ORIENTATION AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS MODERATING VARIABLE: A Survey on Employees of Sukoharjo Primary Tax Service Office - Wahyuningsih, Fitri; Suprayitno, Suprayitno; Palupi, Dyah Ayu Puri (UTSAHA: Journal of Entrepreneurship, 2024)
The main improvement a company needs to do if it is to expand its business is improving their human resources. One of these improvements is through the implementation of work orientation and organizational culture. Therefore, this research was conducted to examine the impact of work orientation and organizational culture on employee performance using motivation as moderating variable  at the Primary Tax Service Office, Sukoharjo. The research method used is a survey based on the Proportionate Cluster Random Sampling technique conducted on 59 respondents of Primary Tax Service Office, Sukoharjo. The data analysis techniques that was applied consist of multiple linear regression, t-test, F-test, coefficient of determination, instrument test, classical assumption test, and absolute difference test. Based on the research conducted, may be specified that work orientation has been significantly positive influenced employee performance, while organizational culture has negatively and insignificantly influenced employee performance. Meanwhile, motivation has significantly influenced employee performance and is proven to not moderate both organizational culture as well as work orientation.